The Analysis Of Competence And Career Development Impact On Work Motivation And Its Implication Toward Employee’s Performance - Nuriman, Hasmi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
This study aimed to analyze and prove the influence of competence and career development on work motivation and its implication toward employee’s performance of education and culture affairs offices at Banten province, both partially and simultaneously. The method used in this research were descriptive, survey and explanatory method with population size of 1.406 and sample size of 210 respondents. The method used to analysis data was SEM (Structural Equation Modeling). The research result, obtained the findings as follows: 1). Competence had significant effect on work motivation, 2). Career development had significant effect on work motivation, 3). Competence and career development are jointly significant effect against the work motivation. Partially competence dominantly significant effect on work motivation. 4). Competence had significant effect toward performance, 5). Career development had significant effect toward performance, 6). Work motivation had significant effect toward performance, 7). Competence, motivation and career development simultaneously had significant effect toward performance. Viewed as partial, Competence had dominantly toward employee’s performance. Concerning on direct and indirect effect that work motivation was being partial mediating. The study recommends that in order to improve employee’s performance which reflected by the dimension aspects of the quantity increased work motivation which reflected by the dimension needs to be affiliated and supported by increased competence reflected by the dimension of the ability and do repairs on a career development system reflected the dimension of chance of education and Training.